The potential benefits of Lactobacillus farraginis and Enterococcus durans, isolated from kefir, as probiotic candidates on innate immune responses, expression of some immune genes, and resistance to Lactococcosis disease in juvenile rainbow trout. (27th June 2021) - Ali, Mohsen; Soltanian, Siyavash; Mirghaed, Ali Taheri; akhlaghi, Mostafa; Hossein Hoseinifar, Seyed
Abstract: The present research has investigated the effect of Lactobacillus farraginis (LF) and Enterococcus durans (ED), isolated from kefir, as probiotic on innate immune parameters and expression of IL‐1β and TNF‐1α lysozyme genes in the intestine, as well as resistance to the Lactococcosis in rainbow trout. Four hundred and eighty juveniles (41.9 ± 2.4 g) were divided into eight groups with three replications, including the control, LF1 and LF2 supplemented with 10 7 and 10 8 Cfu/g feed of each strain, Bactocell equivalent to 10 10, ED1 and ED2 with 10 7 and 10 8 Cfu/g feed of each strain, combination supplements LF1+ED1 and LF2+ED2 with 5 × 10 6 and 5 × 10 7 Cfu/g feed of each strain. Compared to control, a significant increase ( p < 0.05) was observed in in serum lysozyme, ACH50, C3 and C4, total antibody, bactericidal activities and blood phagocytosis in LF2, Bactocell, LF2+ED2, and ED2 treatments. Besides, lysozyme gene expression in the intestinal tissue of fish treated with LF2, ED2, and Bactocell significantly increased ( p < 0.05). A significant increase in TNF‐1α gene expression was also observed in all treatments except LF1 and ED1 ( p < 0.05). Moreover, a significant increase in the level of IL‐1β gene expression was observed in all groups, except for ED1 and LF1+ED1, in comparison to the control treatment. After challenge with Lactococcus garvieae, the lowest mortality percentages were recorded for LF2, Bactocell, LF2+ED2, and ED2 treatment compared to the control. The results suggest beneficial effects of kefir derived LAB strains on immune responses, immune‐related genes expression, and disease resistance in rainbow trout.